Dynamics of macrozoobenthos in the Southern Bulgarian Black Sea coastal and open-sea areas - STOYKOV, S.; UZUNOVA, S. (Mediterranean Marine Science, 2001)
The paper presents results of analysis of 96 macrozoobenthic samples, collected on a seasonal basis in Bourgas Bay and in open-sea areas offshore Cape Emine (Bulgarian Black Sea) in 1996 and 1998. In total 96 taxa were established, distributed in four groups: Polychaeta, Mollusca, Crustacea and “Diversa”. The average density of populations was 1756 ind.m-2 with a predominating abundance of Polychaeta species. The average biomass estimated was 183.02 g.m-2, formed mainly by representatives of Mollusca. The latter species were measured together with the shells, which appraised their individual weights. Seven of the species found had a coefficient of constancy more than 50%. These were the most adapted species to the environmental conditions of the investigated areas. The quantitative and qualitative assessments in this study demonstrate an increasing tendency in the parameters obtained (density, biomass, species diversity) in comparison with previous investigations in the early 1990-s, when intensive anthropogenic influence was widely perceived to misbalance the Black Sea ecosystem. The method of Warwick (1986) applied to characterize the water quality of the studied areas allowed us to define them as rather clean or moderately polluted aquatories.